Word Formation of Dialect Verb Derivatives Motivated by Nouns (on Material of Vocabulary of Amur Region Russian Dialects) - V. T. Sadchenko (Научный диалог)
The analysis of word-formation types of verbal vocabulary on the dialect material of little studied in this aspect-Russian dialects of the Amur region is presented. They belong to the resettlement dialects of secondary formation and are characterized by diversity, high variability and peculiarities of functioning in conditions of long-term inter-project contact on a vast territory. The study of verbal vocabulary in the Russian dialects of the Amur region in the word-formation aspect was not carried out systematically. For the first time on this material the group of derived verbs motivated by a noun is considered. The classification of word-formative types and models of dialect verbal derivatives in comparison with literary analogues is proposed, which allows to identify cases of “out-of-type” word-formation determined by the peculiarities of motivating stems and additional components of the meanings of word-formants. It is concluded that word formation in this group of dialects is a peculiar form of manifestation of specific and all-Russian word-formation tendencies. The relevance of the study is due to the fact that the study of this group of dialects in the word-formative aspect is necessary for the construction of the typology of dialects of the Far East, their monographic description, identification of the features of the language in the aspect of its regional existence and reconstruction of the structure of the Russian dialect space as a whole.